(3OhQ gjFI JShjI GdefGRYGJ GdJGHYI defXeI GdJLGQI GdYGdejI ai JaSjQ h JWhjQ bhGYO GdJLGQI GdOhdjI (B/ s - (3TQja YeQ eMeO GdUGhis; (3eMeO SGeM YeQhs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3Jbhe GdCLgRI THg GdbVGFjI ai efXeI GdJLGQI GdYGdejI HGdJWhjQ ef NdGd bjGegG HJaSjQ bhGYO GdfXGe GdJLGQI GdYGdei GdeJYOO GdCWQGa GdLOjO(B: (3aGdJaSjQ h GdJWhjQ geG hLgGf dYedI hGMOI(B. (3h GdWQjbI GdJi JJHYgG GdCLgRI THg GdbVGFjI ai GdJaSjQ JDKQ Ydi OQLI GdJWhjQ (B: (3aGdYdGbI HjfgeG gi YdGbI WQOjI(B. (3h GdbhGYO GdeJHYI ai GdfWGb GdOhdi dJaSjQ GdGJaGbjGJ GdOhdjI gi OGFeB bhGYO hGMOI JWHbgG cd GdeMGad GdOhdjI GdeYfjI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B482-493s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3bhGYO GdJLGQI GdOhdjIs; (3efXeI GdJLGQI GdYGdejIs; (3gjFI JShjI GdefGRYGJs; (3LgGR GdGSJFfGa GdOGFe s; (3gGeT GdEZQGb s; (3GJaGbjI ecGaMI GdEZQGb s; (3MLe GdhGQOGJ GdeZQbI s; (3OYe GdJUOjQs; (3GdSdY GdeMdjI s; (3GdSdY GdeSJhQOI s; (3GJaGb GdhbGjIs; (3GdCLgRI THg GdbVGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs